2006
DOI: 10.1007/s10162-005-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Cells in Auditory Cortex that Project to the Cochlear Nucleus in Guinea Pigs

Abstract: Fluorescent retrograde tracers were used to identify the cells in auditory cortex that project directly to the cochlear nucleus (CN). Following injection of a tracer into the CN, cells were labeled bilaterally in primary auditory cortex and the dorsocaudal auditory field as well as several surrounding fields. On both sides, the cells were limited to layer V. The size of labeled cell bodies varied considerably, suggesting that different cell types may project to the CN. Cells ranging from small to medium in siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…It is unlikely that axons of layer VI cells travel through the IC to terminate at more caudal levels. The auditory cortex projects to a number of subcollicular targets in guinea pigs (Jacomme et al, 2003; Coomes and Schofield, 2004; Schofield et al, 2006; Peterson and Schofield, 2007). All these studies, which include experiments with the tracers used here, have identified layer V cells as the source of the projections to targets caudal to the IC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that axons of layer VI cells travel through the IC to terminate at more caudal levels. The auditory cortex projects to a number of subcollicular targets in guinea pigs (Jacomme et al, 2003; Coomes and Schofield, 2004; Schofield et al, 2006; Peterson and Schofield, 2007). All these studies, which include experiments with the tracers used here, have identified layer V cells as the source of the projections to targets caudal to the IC.…”
Section: Discussionmentioning
confidence: 99%
“…The borders of cortical laminae were added by comparison with adjacent thionin-stained sections or by removing the coverslips from the plotted sections, re-hydrating them, staining them with thionin, and re-applying coverslips. The layers were identified according to criteria described previously (Schofield et al, 2006). In cases with CTB injections, well-labeled cells were drawn with a camera lucida attached to a Zeiss Axioskop.…”
Section: Methodsmentioning
confidence: 99%
“…A change in the balance between LTP and LTD may explain the decreased responsiveness of ACx in sound-deprived mice (21) and the decline of electrically evoked responses observed in congenitally deaf cats (45). L5 synaptic plasticity may have a significant impact on subthalamic processing because of the massive descending projection from ACx (28,(46)(47)(48)(49)(50). Furthermore, the specific complement of cortical plasticity mechanisms may support the functional takeover of ACx by other sensory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pyramidal cell axons from the A1auditory cortex distribute specifically to the granule cell domain of the cochlear nuclear complex in mouse, rat gerbil and guinea pig (Feliciano et al, 1995; Weedman and Ryugo, 1996a,b; Budinger et al, 2000; Jacomme, 2003; Schofield and Coomes, 2005a,b; Schofield et al, 2006a,b; Meltzer and Ryugo, 2006). In the hedgehog tenrec a similar projection seems to arise from the somatosensory cortex (Wolff and Künzle, 1997).…”
Section: The Fibers Targeting Ubcs In Cerebellum and Cochlear Nucleusmentioning
confidence: 99%